Qualidade do atendimento hospitalar no Rio Grande do Norte: avaliação de usuários e acompanhantes - Silva Júnior, Danyllo do Nascimento (2018)
Evaluation in the health area has gained more and more space in the international and national scenario, with quality being one of the strategic elements on which the transformation and improvement of modern health systems is based. This research had the general objective of analyzing the perceptions of users and companions about the quality of hospital care in Rio Grande do Norte. In order to do so, the methodological approach was guided by the following steps: (a) a cross-sectional analytical study to evaluate the SUS users' satisfaction about hospital and outpatient care, with reference to the physical structure, health and the quality of treatment received in Rio Grande do Norte services; and (b) to carry out an exploratory and qualitative case study carried out in hospitals, which aimed to evaluate the satisfaction of users and caregivers with the quality of care in public hospitals in Rio Grande do Norte, Brazil. The results showed that there was no difference in the evaluation of services when compared to men and women; people over 60 tend to better evaluate health services; in all aspects the high complexity and services of the capital had better results (p≤0.001) and the users evaluated more positively the service rendered by the private units agreed to the SUS than the public establishments. Regarding the qualitative findings, it was noticed that users and caregivers were generally satisfied with the care provided by public hospitals within the Unified Health System, especially regarding aspects related to the humanization of health teams and the effectiveness of the process. In this context, the positive view of the interviewees in this study on public hospitals is highlighted, even considering aspects considered negative that affect the quality of care of these services and that were raised by the interviewees themselves, such as the physical facilities conditions, lack or insufficient material resources and bureaucracies that delay the therapeutic path. As expected, the qualitative approach allowed a deepening around the findings of the quantitative approach. While it identified the generic satisfaction about the quality of care, it allowed the subjects to clarify in more detail the reasons why the services were considered good or bad. It is concluded that the evaluation of the quality of hospital care from the point of view of subjects who use this service is essential for the survey of aspects that deserve attention by health authorities and managers and related areas. Thus, it is expected that the findings of this study make possible reflections, as well as emphasizing the indispensability of further research in this sense in order to provide subsidies capable of overcoming problems and improving the services offered to the population.